Disposition of emergency department patients presenting with angiotensin-converting enzyme inhibitor-induced angioedema - Blake Briggs; David Cline; Iltifat Husain (International Journal of Emergency Medicine)
Abstract Background Angiotensin-converting enzyme inhibitors (ACEI) are the most common cause of drug-induced angioedema in the United States. Our primary objective was to provide descriptive evidence regarding emergency department (ED) disposition of ACEI-induced angioedema patients. Our secondary objective was to evaluate unique patterns in those with ACEI-induced angioedema at a tertiary referral center, including demographics, details of those requiring intubation, length of inpatient stay, and allergy documentation. Methods This was a retrospective study evaluating all cases of ACEI-induced angioedema at a large, regional academic medical center. We performed a medical record review to identify patients with ACEI-induced angioedema who presented to the ED from January 1, 2016, to December 31, 2022. A structured data abstraction process was utilized to select patients of interest, followed by descriptive statistics, chi-square tests and odds ratios for categorical data, and Kruskal Wallis tests for continuous data. Results A total of 637 unique patient encounters met potential inclusion. After a substantial, standardized review, 94 patients met inclusion. During the study period, there were 94 patients presenting to the ED who were diagnosed as having angioedema secondary to an ACEI (90 patients) or angiotensin receptor blocker (ARB) (4 patients). Overall, 53 patients (56.38%) improved during their ED stay, and of those, 32 patients (60.38%) were discharged home. None of the 12 patients that worsened were sent home from the ED. Those who were discharged from the ED with a median stay of 4 h had no increased risk of return to the ED versus those who were admitted. The only treatment found to have statistical association with disposition was intramuscular epinephrine. Only 13 of 43 ED discharged patients (23.64%) had their ACEI/ARB documented in their allergy listings compared to 42 of 51 patients (76.36%) of admitted patients, odds ratio of failure to document was 0.0929 (95% CI, 0.0352 to 0.24512). Only one patient out of the total 94 returned to the ED due to recurrent angioedema symptoms during our study period and was subsequently discharged. Conclusion Our results indicated that at a large, tertiary care referral center, patients with ACEI-angioedema who did not exhibit severe symptoms were safely discharged home with low risk of early return visit to the ED. Severe symptoms were found to be any throat symptoms, voice change, drooling, worsening swelling, or complaints of dyspnea. Further, among those admitted, patients in our study had a short inpatient stay and were safely discharged with no documented early return visit to the ED.